Design, Development and Control of a Hopping Machine – an Exercise in Biomechatronics - Kuldip Naik; Mehran Mehrandezh; John Barden (Applied Bionics and Biomechanics)
Hopping is a complicated dynamic behaviour in the animal kingdom. Development of a hopping machine that can mimic the biomechanics of jumping in Homo sapiens is envisioned. In this context, the design, development and control of a cost-effective, pneumatically actuated, one-legged hopping machine were initiated at the University ofRegina in 2005. The pneumatic actuator has a simple design that employs an off-the-shelf on/off control valve which regulates the air pressure supplied to the hopper's body using a pulse width modulated (PWM) signal. The objective is to maintain a constant jumping height in the hopper after going through a finite number of hopping cycles. The mechanistic model of the system was investigated in full detail. This model facilitates: (1) the design of the actuating system, and (2) the synthesis and verification of different control strategies in a simulation environment prior to implementation in the real world. The movement of the hopper is supported by a vertical slide; therefore, the hopper can only jump in place. However, the proposed control strategy and the propulsion unit can be further utilised for stable hopping in a 3-D environment. A model-free Neuro-PD controller was then designed, trained and implemented on a real system. Simulation and experimentation showed promising results. This system can be used as an educational tool for teaching real-time control of hybrid and non-linear systems. It can be also used as a biomechatronics test bed to simulate the effect of different timings in firing action potentials in jump-causing leg muscles on achieving a desired jumping height in the animal kingdom.